Sherlock. A study in pink - Moffat, Steven, 1961-; Jay, (Jay Henning) (Titan Comics, 2017)
"Holmes and Watson tackle brain-teasing crimes in modern-day London in this stunning Manga, presented in its original right-to-left reading order, and in the full chapters as originally serialized! Meet Holmes and Watson for the first time... all over again!"--Amazon.com